ANALISIS ETIKA BISNIS ISLAM TERHADAP MEKANISME PENETAPAN HARGA LELANG BARANG AGUNAN DI BANK KB BUKOPIN SYARIAH SURABAYA - Hafiya, Hafiya; Ersya Faraby, Muhammad (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
This research aims to understand Islamic business ethics related to executing the auction price determination method by the KB Bukopin Syariah Bank of Surabaya. This research uses a qualitative descriptive methodology, explicitly focusing on describing and analyzing the process of determining auction prices. This research indicates that the stages in determining the auction price carried out by the KB Bukopin Syariah Bank of Surabaya through the State Property and Auction Services Office are based on Sharia principles. KB Bukopin Syariah Bank adheres to Sharia economic guidelines in determining prices that align with established mechanisms. KB Bukopin Syariah Bank supervises central markets, regional markets, and local markets to mitigate the possibility of price manipulation carried out by irresponsible individuals. Apart from that, KB Bukopin Syariah Bank also carries out evaluations so that customers do not experience losses related to the collateral that will be auctioned.